Improved of Stair Climbing Wheelchair for Differently Abled People - Jose, Arun; Leneesh N, Gopal; Jishnu, M; Harikrishnan, AR (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a new version of Wheelchair’s, a wheelchair with stair climbing ability. The wheelchair is able to climb single obstacles or staircases thanks to a hybrid wheel- leg locomotion unit with a triple-wheels cluster architecture. The new concept presented in this work represents an improvement respect to previous versions. Through a different arrangement of functional elements, the wheelchair performances in terms of stability and regularity during movement on stair have been increased. In particular, attention has been paid to ensure a regular and comfortable motion for the user during stair climbing operation. For this reason, a cam mechanism has been introduced and designed with the aim to compensate the oscillation generated on the wheelchair frame by the locomotion unit rotation. A design methodology for the cam proﬁle is presented. Moreover, a para- metric analysis on the cam proﬁle and on the mechanism dimensions has been conducted with the aim to ﬁnd a cam proﬁle with suitable dimensions and performances in terms of pressure angle and radius of curvature.